Widely targeted metabolome profiling of different plateau raspberries and berry parts provides innovative insight into their antioxidant activities - Ren, Xiaoli; Wang, Shulin; Wang, Jinying; Xu, Dan; Ye, Ying; Song, Yangbo (Frontiers in Plant Science, 2023)
Raspberries are considered worldwide as functional berries due to their excellent nutritional value and strong antioxidant activities. Whole raspberry or its parts favorably influence physiological functions via various biological metabolisms. However, plateau raspberries and phytochemicals in whole berries and their different parts have been less reported than in other berries. To confirm the diversity and variability of metabolites in whole raspberry and its parts and disclose critical metabolites and pathways contributing to differences in antioxidant activities, commercial raspberries and their pulp and seed from two plateaus (Yunnan and Qinghai, China) were subjected to LC-MS/MS-based widely targeted metabolomics analysis. Moreover, the antioxidant activity of raspberry and its fractions was also measured by four methods, including DPPH, ABTS, FRAP, and ORAC assays. 1661 metabolites were identified and chemically classified into 12 categories. The composition of metabolic compounds varied significantly with the whole berry, parts, and plateaus. Compared with Yunnan raspberry, many flavonoids, amino acids and their derivatives, and phenolic acids were up-regulated in Qinghai’s raspberry. 246 key differential metabolites were filtered out. Flavonoid biosynthesis, flavone and flavonol biosynthesis, biosynthesis of amino acids, and anthocyanin biosynthesis were the main differently regulated pathways. The DPPH, FRAP, ABTS, and ORAC assays showed that the antioxidant activity of Qinghai raspberry was stronger than Yunnan’s. The environment, in which the berries grow, can result in variations in their chemical composition. The Qinghai raspberry might be related to its high content of flavonoids, amino acids and their derivatives, and phenolic acids mainly. In addition, the order of the antioxidant capacity was seed > pulp > berry. The highest DPPH and FRAP value were found in the seed of Qinghai raspberry (5218.34 μg TE/g FW, 420.31 µM TE/g DW). By antioxidant activity and correlation analysis, we found that Qinghai raspberry seed contained the most specific metabolites, such as flavonoids, fatty acids, tannins, and phenolic acids. Collectively, phytochemical compositions and antioxidant activity in whole raspberry, berry parts, and plateaus expand comprehensive exploitation and cultivation.